AB0716 Predictive Value of DLCO Reduction in Scleroderma Patients Without Cardio-Pulmonary Involvement at Baseline. (9th June 2015) - Colaci, M.; Giuggioli, D.; Sebastiani, M.; Manfredi, A.; Lumetti, F.; Luppi, F.; Cerri, S.; Ferri, C.
Abstract : Background: Impaired diffusing capacity of the lung for carbon monoxide (DLCO) was frequently observed in systemic sclerosis (SSc) patients, generally related to the presence of interstitial lung disease (ILD) and/or pulmonary arterial hypertension (PAH). However, in clinical practice abnormally low DLCO values may be found also in the absence of these SSc complications. Objectives: To investigate the prospective clinical relevance of isolated DLCO reduction at baseline in SSc patients. Methods: Ninety-seven SSc female patients (age at the diagnosis: 51.3±14.5 years; disease duration: 10.4±6.6 years; limited/diffuse skin subsets: 92/5), without any clinical, radiological (high resolution computed tomography), and echocardiographic manifestations of ILD or PAH at baseline, nor other lung or heart diseases able to affect DLCO, were recruited at our Rheumatology Centre. Patients with DLCO <55% 1 (15 patients; group A) were compared with those with normal DLCO (82 patients; group B), at baseline and at the end of follow-up. Results: At baseline, patients of group A showed significantly higher percentage of anticentromere autoantibodies compared to group B (13/15, 86.6% vs. 48/82, 58.5%; p=0.044). More interestingly, at the end of long-lasting clinical follow-up (11.6±6.7 years), pre-capillary PAH (right heart catheterization) solely developed in some patients of group A (3/15, 20% vs. 0/82; p=0.003). Conclusions: In SSc patients, the presence at baseline of isolated, marked DLCO reduction (<55% of predicted) and serum anticentromere autoantibodies might characterize a peculiar SSc subset that may precede the development of PAH. Therefore, careful clinical follow-up of patients with isolated moderate-severe DLCO reduction should be mandatory. References: Steen VD, Graham G, Conte C, Owens G, Medsger TA Jr. Isolated diffusing capacity reduction in systemic sclerosis. Arthritis Rheum 1992; 35:765-70. Disclosure of Interest: None declared